The SIH-EBP Score: A grading scale to predict the response to the first epidural blood patch in spontaneous intracranial hypotension. (March 2023) - Lin, Po-Tso; Wang, Yen-Feng; Hseu, Shu-Shya; Fuh, Jong-Ling; Lirng, Jiing-Feng; Wu, Jr-Wei; Chen, Shu-Ting; Chen, Shih-Pin; Chen, Wei-Ta; Wang, Shuu-Jiun
Background: To develop and validate an easy-to-use scoring system to predict the response to the first epidural blood patching in patients with spontaneous intracranial hypotension. Methods: This study recruited consecutive patients with spontaneous intracranial hypotension receiving epidural blood patching in a tertiary medical center, which were chronologically divided into a derivation cohort and a validation cohort. In the derivation cohort, factors associated with the first epidural blood patching response were identified by using multivariable logistic regression modeling. A scoring system was developed, and the cutoff score was determined by using the receiver operating characteristic curve. The findings were verified in an independent validation cohort. Results: The study involved 280 patients in the derivation cohort and 78 patients in the validation cohort. The spontaneous intracranial hypotension-epidural blood patching score (range 0–5) included two clinical variables (sex and age) and two radiological variables (midbrain-pons angle and anterior epidural cerebrospinal fluid collections). A score of ≥3 was predictive of the first epidural blood patching response, which was consistent in the validation cohort. Overall, patients who scored ≥3 were more likely to respond to the first epidural blood patching (odds ratio = 10.3). Conclusion: For patients with spontaneous intracranial hypotension-epidural blood patching score ≥3, it is prudent to attempt at least one targeted epidural blood patching before considering more invasive interventions.